PVA optical film for polaroid without in-plane linear light leakage and preparation method of PVA optical film

By using low bubble surfactant and optimized process parameters during the preparation of PVA optical film, the problem of bubble generation is solved, and the quality of the film and the performance of the polarizer are significantly improved.

CN119773282AActive Publication Date: 2025-04-08ANHUI WANWEI UPDATED HIGH TECH MATERIAL CO LTD +1
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202510070676.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-16
Publication Date
2025-04-08
Estimated Expiration
2045-01-16

AI Technical Summary

Technical Problem

During the preparation of PVA optical film, it is difficult to effectively reduce the generation of bubbles, resulting in the appearance of through-type scattered defects on the film surface, affecting the color rendering performance and yield of the polarizer.

Method used

The low-bubble surfactant formula, dissolution extrusion defoaming process, film-forming water control process and other technical means are adopted to control the foaming and defoaming capacity of the surfactant, optimize the defoaming time and temperature, adjust the parameters of the extruder, and control the moisture content of the film to reduce the generation of bubbles.

Benefits of technology

It effectively reduces the number and size of bubbles in the PVA optical film, improves the apparent performance and tensile performance of the film, and thus improves the quality and yield of the surfaceless linear light leakage polarizer.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119773282A_ABST
    Figure CN119773282A_ABST
Patent Text Reader

Abstract

The invention discloses a PVA optical film for a polarizer without in-plane linear light leakage and a preparation method of the PVA optical film, and relates to the technical field of PVA optical films.The method comprises the steps that PVA, a plasticizer, a surfactant with the solution foaming capacity Hb smaller than or equal to 40 mm and the solution defoaming capacity Hd smaller than or equal to 10 mm and an antioxidant are added into deionized water together to be evenly dissolved, and a film casting stock solution is obtained; the preparation method comprises the following steps: stirring and defoaming the casting film stock solution, extruding and defoaming through a three-section type extruder, carrying out tape casting through a die head to form a thin film, pre-drying through a tape casting roller and a drying roller, carrying out heat treatment, drying and shaping, and finally rolling to obtain the PVA optical film. By controlling the solution foaming capacity and the solution defoaming capacity of the surface defoaming agent, bubble elimination is carried out on the PVA optical film, meanwhile, parameters such as defoaming time and temperature and inlet pressure of a GP pump are controlled, technological parameters are optimized, then the bubble content in a film casting stock solution is eliminated, and the PVA optical film for the polaroid free of in-plane linear light leakage is obtained, and the PVA optical film is small in bubble amount, high in quality and free of in-plane linear light leakage.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of optical films, and in particular to a PVA optical film for a polarizer without in-plane linear light leakage and a preparation method thereof. Background Art

[0002] Polyvinyl alcohol optical film is mainly used in the production of polarizers, and the end products are various types of liquid crystal displays, such as display panels for televisions, computer monitors, mobile phones, car navigation and wearable electronic devices. PVA polarizers are made by swelling, dyeing, uniaxial stretching, boride cross-linking, and laminating triacetate cellulose TAC film with PVA optical film. As display panels develop towards thinner, more durable, and more transparent directions, especially in automotive applications, higher and higher requirements are placed on the quality of polyvinyl alcohol polarizers and their upstream PVA optical films.

[0003] PVA polarizer is made of PVA optical film after highly stretched, iodine dyed and cross-linked with boric acid. The PVA optical film is made by processes such as PVA dissolution, extrusion, casting and drying. During the dissolution and stirring process, the gas in the kettle is continuously stirred into the solution. As the PVA is completely dissolved, the viscosity of the solution gradually increases. The stirred gas is difficult to be quickly removed by buoyancy. Finally, the PVA solution contains a large number of bubbles, which are extruded and cast and remain on the PVA film. When the bubbles are large, they break, especially when processing thin PVA optical films, forming through-type scattered point defects, resulting in slender light leakage in the polarizer prepared after stretching and dyeing, which is the main reason for limiting the color performance and yield of thin polarizers. Summary of the invention

[0004] The object of the present invention is to provide a PVA optical film for a polarizer without in-plane linear light leakage and a preparation method thereof, so as to solve the following technical problems:

[0005] How to reduce bubbles generated during the formation of PVA film.

[0006] The purpose of the present invention can be achieved through the following technical solutions:

[0007] In a first aspect, the present invention discloses a method for preparing a PVA optical film, which uses a series of preparation technologies such as a low-bubble surfactant formula, a dissolution extrusion defoaming process, and a film-forming water content control process to reduce the generation of bubbles, and specifically includes the following steps:

[0008] S1. Add the raw materials together into deionized water and uniformly dissolve them to obtain a casting solution; wherein the raw materials include 60-80 parts of PVA, 6-8 parts of plasticizer, 2-4 parts of surfactant with a solution foaming capacity Hb≤40mm and a solution defoaming capacity Hd≤10mm, and 2-4 parts of antioxidant in parts by weight, and the mass fraction of the raw materials in the casting solution is 20-37%;

[0009] like Figure 1 As shown (taking a certain surfactant as an example), the foaming ability and defoaming ability of the surfactant solution can be determined by the following method:

[0010] Step 1: Configure the concentration to 4.0×10 -4 g / mL, 5mL of surfactant solution is placed in a sample bottle with a height of 7.5cm, an outer diameter of 2.5cm, and a capacity of 15mL. The sample bottle is placed on the test table. Figure 1 As shown, the test table should be horizontal, with a black background and a ruler to read the initial height H0 of the surfactant solution;

[0011] Step 2: Wrap the sample bottle containing the surfactant solution to be tested in a dust-free cloth and put it into the centrifuge. Set the centrifuge speed to 3000r / min and the time to 5min. When using the centrifuge, pay attention to symmetrical placement and uniform weight;

[0012] Step 3: After centrifugation, take out the sample bottle and quickly place it in front of a black background to read the height H1 of the surfactant solution (the highest position caused by bubbles). The foaming performance of the surfactant solution is measured by Hb=H1-H0. The larger the Hb value, the better the foaming performance.

[0013] Step 4: After standing for 2 hours, read the bubble height as H2, and measure the defoaming performance of the surfactant solution as Hd=H1-H2. The larger the Hd value, the better the defoaming performance.

[0014] S2. Stir and degas the casting solution at 130-160°C at a rate of 5-20Hz for 1-3h. If the temperature is too low, the stirring is too fast, or the time is too short, it will not be conducive to degassing, and will result in a large amount of bubbles in the casting solution, affecting the apparent properties and tensile properties of the film. Then, the film is extruded and degassed through a three-stage extruder, and a film is formed through die casting. After pre-drying by a casting roller and a drying roller, the film is subjected to heat treatment, drying and shaping, and finally rolled up to obtain the PVA optical film.

[0015] in:

[0016] In step S1, the reason for controlling the foaming ability of the surfactant to be ≤40mm is that excessive foaming ability will lead to excessive number of bubbles in the solution, affecting the surface performance and optical properties of the film; the reason for controlling the defoaming ability of the surfactant to be ≤10mm is that excessive defoaming ability will lead to excessive number of bubbles still existing in the solution, affecting the surface performance and tensile properties of the film.

[0017] In step S2,

[0018] After being dried by the casting roller, the moisture content of the film is controlled to be 20-30%; after being dried by the drying roller, the moisture content of the film is controlled to be 8-15%; after being heat-treated, dried and finalized, the moisture content of the film is controlled to be 0.1-5%, preferably 0.5-3%; if the moisture content of each section is too low, it will not be conducive to the formation of a uniform and dense PVA crystal network, which will lead to the poor stability of the prepared PVA optical film crystals and chemical cross-linking network; if the moisture content is too high, it will easily cause the evaporation of the solvent in the liquid film and also cause bubbles on the film surface.

[0019] Furthermore, the PVA includes at least one of a polyvinyl alcohol homopolymer and a polyvinyl alcohol copolymer modified product.

[0020] Preferably, the modified monomer in the polyvinyl alcohol copolymer modified product includes at least one of hydrocarbons, acrylates, methacrylamide derivatives, vinyl esters, and vinyl halides.

[0021] More preferably, the hydrocarbons include ethylene and propylene; the acrylates include methyl acrylate; and the methacrylates include methyl methacrylate.

[0022] Furthermore, the content of the modified groups in the PVA is less than 10%; the average polymerization degree of the PVA is 1500-3000; and the alcoholysis degree of the PVA is 98%-99.99%.

[0023] Preferably, the alcoholysis degree of the PVA is 99%-99.99%. If the alcoholysis degree is too low, the solubility of the PVA in the film casting solution will deteriorate, which will easily lead to instability in the casting production process. Therefore, the alcoholysis degree of the PVA is controlled at a relatively high level.

[0024] Furthermore, the plasticizer includes at least one of glycerol, diglycerol, polyglycerol, ethylene glycol, and propylene glycol.

[0025] Furthermore, the surfactant is a mixed surfactant of at least two of nonionic surfactants and / or anionic surfactants.

[0026] Preferably, the nonionic surfactant includes alkyl lipids, alkylamines, and alkylamides; the anionic surfactant includes carboxylic acids and dodecylbenzene sulfonate.

[0027] More preferably, the alkyl lipids include polyoxyethylene lauryl ester; the alkyl amines include polyoxyethylene lauryl amino ester; the alkyl amides include polyoxyethylene lauric acid amide; and the carboxylic acids include potassium laurate.

[0028] Preferably, the antioxidant includes any one or more combinations of antioxidant B225, antioxidant 1010, and antioxidant 168.

[0029] Furthermore, in step S2, during extrusion degassing, the barrel temperatures at both ends of the three-stage extruder are lower than the middle barrel temperature, and the middle barrel temperature is 90-130° C. If the middle barrel temperature is too low, it is not conducive to bubble breaking, and if it is too high, it will cause the solution to boil and generate more bubbles.

[0030] Further, in step S2, when extrusion degassing is performed, the GP pump inlet pressure of the three-stage extruder is 1.5-3MPa. Properly increasing the GP pump inlet pressure can increase the degassing ability, thereby reducing bubbles and reducing the occurrence of bubbles; but if the GP pump inlet pressure is too high, it will cause the extruder to overflow, which is not conducive to the discharge of gas in the bubbles of the extruder solution, and the degassing effect will deteriorate; if the GP pump inlet pressure is too low, it will cause the pressure difference between the head and the exhaust section of the three-stage extruder to decrease, and the gas after the bubble is broken will not be able to be quickly discharged from the exhaust hole, and the degassing effect will also deteriorate.

[0031] Furthermore, in step S2, when performing extrusion degassing, the GP pump speed of the three-stage extruder is 40-80rpm, preferably 50-70rpm; if the speed is too high, the GP pump will not be able to establish inlet pressure, which is not conducive to degassing; if the speed is too low, the transmission efficiency of the GP pump will be reduced, the shearing of the material will be aggravated, which is not conducive to the uniformity of the liquid.

[0032] Furthermore, in step S2, when extrusion degassing is performed, the pipeline temperature from the three-stage extruder to the die head and the die head temperature are 90-110°C; if the temperature is too high, the solution will flash, resulting in excessive bubbles in the film-making solution; if the temperature is too low, the fluidity uniformity of the solution will be poor, which may easily cause more surface defects on the film surface.

[0033] Furthermore, in step S2, the temperature of the casting roller is 88-95°C; if the temperature is too high, the liquid film will boil and generate a large number of bubbles; if the temperature is too low, the liquid film will not be sufficiently dried and the water content will be too high, which will make it difficult for the liquid film to be peeled off from the casting roller and increase the defects on the film surface.

[0034] Furthermore, in step S2, the number of drying tanks is 8-20, the temperature of each roller is 30-90°C, and the temperature distribution shows a gradually decreasing trend; if the temperature is too high, it will be unfavorable for the formation of a uniform and dense PVA crystal network, resulting in poor stability of the prepared PVA optical film crystals and chemical cross-linking network, and poor processing performance; if the temperature is too low, it will be unfavorable for the subsequent heat treatment process, and problems such as dripping water and glycerin may easily occur.

[0035] Furthermore, in step S2, when heat treatment, drying and shaping are performed, a one-stage heat treatment or a multi-stage heat treatment is adopted according to the heat treatment time.

[0036] Preferably, when a multi-stage heat treatment is adopted, the temperature of each stage of the heat treatment tends to first increase and then decrease.

[0037] More preferably, a five-stage heat treatment method is adopted, and the heat treatment time is evenly divided into five sections, the heat treatment temperature of the first section is 50-80°C, the heat treatment temperature of the second section is 55-85°C, the heat treatment temperature of the third section is 70-100°C, the heat treatment temperature of the fourth section is 100-130°C, and the heat treatment temperature of the fifth section is 50-80°C; in the second to fourth sections, if the temperature is too high, the crystal size will be too large, and if the temperature is too low, the total water content will be too high; in the fifth section, it should be slowly lowered to ambient temperature. If the set temperature is too low, glycerol precipitation is likely to occur.

[0038] In a second aspect, the present invention further discloses a PVA optical film for a polarizer without in-plane linear light leakage, which is prepared by the above-mentioned method for preparing the PVA optical film.

[0039] Beneficial effects of the present invention:

[0040] In the preparation method of the PVA optical film of the present invention, bubbles are eliminated from the PVA optical film by controlling the solution foaming ability and solution defoaming ability of the surface defoamer, and at the same time, the degassing time and temperature, GP pump inlet pressure, rotation speed, temperature of each section of the three-stage extruder, temperature of the casting roller and the drying roller, moisture content after drying and other parameters are controlled to optimize the process parameters, thereby eliminating the bubble content in the casting solution, and obtaining a PVA optical film with a small amount of bubbles and high quality for a polarizer without in-plane linear light leakage. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] The present invention will be further described below in conjunction with the accompanying drawings.

[0042] Figure 1 This is an operation diagram for measuring the foaming ability and defoaming ability of a solution of a certain surfactant as an example in the present invention. DETAILED DESCRIPTION

[0043] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0044] The experimental methods in the following examples are conventional methods unless otherwise specified, and are performed according to the techniques or conditions described in the literature in the art or according to the product instructions. The materials, reagents, etc. used in the following examples are all commercially available unless otherwise specified, and the surfactants used are all tested by the above-mentioned methods for testing the foaming ability and defoaming ability of the surfactant solution.

[0045] Example 1

[0046] 2952kg of PVA polymer (average degree of polymerization of 2200, alcoholysis degree of 99%), 126.5kg of sodium dodecylbenzene sulfonate (solution foaming ability of 25mm, solution defoaming ability of 5%), 295kg of glycerol and 126.5kg of antioxidant B225 were put into a reactor with 6500kg of deionized water, and stirred for 6h at 150℃ and 0.4MPa to uniformly dissolve, and a casting solution with a solute content of 35% was obtained; the casting solution was stirred and degassed at 140℃ at a rate of 10Hz for 2h, and then extruded and degassed by a three-stage extruder (the temperature of the barrels at both ends was set to 90℃, and the temperature of the middle barrel was set to 110℃; G / P The pump inlet pressure is controlled at 2MPa; the G / P pump speed is controlled at 60rpm; the pipeline temperature from the three-stage extruder to the die and the die temperature are controlled at 105°C), and a film is formed by die casting, and the moisture content of the film is controlled to be 25% at this time; then it is pre-dried by a 90°C casting roller and 15 50°C drying rollers (the moisture content of the film after the casting roller is 12%, and the moisture content of the film after the drying roller is 2%), and then enters the oven for heat treatment, drying and shaping (five-stage heat treatment is carried out at 65°C, 70°C, 90°C, 120°C, and 70°C, and the time for each heat treatment is 1h), and finally rolled up to obtain the PVA optical film for polarizer with no in-plane linear light leakage.

[0047] Example 2

[0048] 1714 kg of PVA polymer (average degree of polymerization of 2200, alcoholysis degree of 99%), 57.5 kg of sodium dodecylbenzene sulfonate (solution foaming ability of 25 mm, solution defoaming ability of 5%), 171 kg of glycerol and 57.5 kg of antioxidant 1010 were put into a reactor with 8000 kg of deionized water, and stirred for 6 hours at 150 ° C and 0.4 MPa to uniformly dissolve to obtain a casting solution with a solute content of 20%; the casting solution was stirred and degassed at a rate of 20 Hz at 130 ° C for 3 hours, and then extruded and degassed by a three-stage extruder (the temperature of the barrels at both ends was set to 80 ° C, and the temperature of the middle barrel was set to 90 ° C; G / P pump The inlet pressure is controlled at 1.5MPa; the speed of the G / P pump is controlled at 40rpm; the temperature of the pipeline from the three-stage extruder to the die and the temperature of the die are controlled at 90°C), and a film is formed by die casting, and the moisture content of the film is controlled to be 20% at this time; then it is pre-dried by a casting roller at 88°C and 8 drying rollers at 90°C (the moisture content of the film after the casting roller is 8%, and the moisture content of the film after the drying roller is 0.5%), and then enters the oven for heat treatment, drying and shaping (five-stage heat treatment is carried out at 65°C, 70°C, 90°C, 120°C, and 70°C, and the time of each heat treatment is 1h), and finally rolled up to obtain the PVA optical film for polarizer with no in-plane linear light leakage.

[0049] Example 3

[0050] 3083kg of PVA polymer (average degree of polymerization of 2200, degree of alcoholysis of 99%), 154.5kg of sodium dodecylbenzene sulfonate (foaming ability of the solution is 25mm, defoaming ability of the solution is 5%), 308kg of glycerol and 154.5kg of antioxidant mixture were put into a reactor with 6300kg of deionized water, and stirred for 6h at 150°C and 0.4MPa to uniformly dissolve, and a casting solution with a solute content of 37% was obtained; the casting solution was stirred and degassed at 160°C at a rate of 5Hz for 1h, and then extruded and degassed by a three-stage extruder (the temperature of the barrels at both ends was set to 100°C, and the temperature of the middle barrel was set to 130°C; G / The inlet pressure of the P pump is controlled at 3MPa; the speed of the G / P pump is controlled at 80rpm; the temperature of the pipeline from the three-stage extruder to the die and the temperature of the die are controlled at 110°C), and a film is formed by die casting, and the moisture content of the film is controlled to be 30% at this time; then it is pre-dried by a 95°C casting roller and 20 30°C drying rollers (the moisture content of the film after the casting roller is 15%, and the moisture content of the film after the drying roller is 3%), and then enters the oven for heat treatment, drying and shaping (five-stage heat treatment is carried out at 65°C, 70°C, 90°C, 120°C, and 70°C, and the time of each heat treatment is 1h), and finally rolled up to obtain the PVA optical film for polarizer with no in-plane linear light leakage.

[0051] Example 4

[0052] Compared with Example 1, the only difference is that: when the film is formed by die casting, the moisture content of the film is controlled to be 20%, the moisture content of the film after passing through the casting roller is 8%, and the moisture content of the film after passing through the drying roller is 0.1%; the other steps and conditions remain the same, and finally a PVA optical film for a polarizer without in-plane linear light leakage is obtained.

[0053] Example 5

[0054] Compared with Example 1, the only difference is that: when the film is formed by die casting, the moisture content of the film is controlled to be 30%, the moisture content of the film after passing through the casting roller is 15%, and the moisture content of the film after passing through the drying roller is 5%; the other steps and conditions remain the same, and finally a PVA optical film for a polarizer without in-plane linear light leakage is obtained.

[0055] Comparative Example 1

[0056] Compared with Example 1, the only difference is that the surfactant is replaced by sodium dodecylbenzene sulfonate (the solution foaming capacity is 45 mm, and the solution defoaming capacity is 5%), and the other steps and conditions remain the same, and finally a PVA optical film for a polarizer without in-plane linear light leakage is obtained.

[0057] Comparative Example 2

[0058] Compared with Example 1, the only difference is that the surfactant is replaced by sodium dodecylbenzene sulfonate (the solution foaming capacity is 40 mm, and the solution defoaming capacity is 15%), and the other steps and conditions remain the same, and finally a PVA optical film for a polarizer without in-plane linear light leakage is obtained.

[0059] Comparative Example 3

[0060] Compared with Example 1, the only difference is that the surfactant is replaced by sodium dodecylbenzene sulfonate (the solution foaming capacity is 45 mm, and the solution defoaming capacity is 15%), and the other steps and conditions remain the same, and finally a PVA optical film for a polarizer without in-plane linear light leakage is obtained.

[0061] The PVA optical films for polarizers without in-plane linear light leakage prepared in Examples 1-5 and Comparative Examples 1-3 were subjected to a bubble evaluation test. The test method is as follows: the PVA optical film within a range of 100 m in length and 3.4 m in width was tested using a defect detector. The bubbles were intuitively manifested as primary defect black spots on the defect detector. The number of black spots within the range (i.e., the number of bubbles) was recorded, and the diameter of the black spots (i.e., the diameter of the bubbles) was measured. The test results are listed in Table 1. Table 1 is as follows:

[0062] Table 1

[0063]

[0064] By analyzing the data in Table 1, it can be found that compared with comparative examples 1-3, the amount of bubbles and the size of bubbles in the PVA optical films of embodiments 1-5 are significantly lower, which indicates that the preparation method of the PVA optical film of the present invention can produce a PVA optical film with better performance for polarizers without in-plane linear light leakage.

[0065] The above is a detailed description of an embodiment of the present invention, but the content is only a preferred embodiment of the present invention and cannot be considered to limit the scope of implementation of the present invention. All equivalent changes and improvements made within the scope of the present invention should still fall within the scope of the patent coverage of the present invention.

Claims

1. A method for preparing a PVA optical film, characterized in that: The steps include: S1. Add the raw materials together into deionized water and uniformly dissolve them to obtain a casting solution; wherein the raw materials include 60-80 parts of PVA, 6-8 parts of plasticizer, 2-4 parts of surfactant with a solution foaming capacity Hb≤40mm and a solution defoaming capacity Hd≤10mm, and 2-4 parts of antioxidant in parts by weight, and the mass fraction of the raw materials in the casting solution is 20-37%; S2, stirring and degassing the film casting stock solution at 130-160° C. at a rate of 5-20 Hz for 1-3 hours, then extruding and degassing through a three-stage extruder, forming a film through a die casting, and then pre-drying through a casting roller and a drying roller, and then entering a heat treatment drying and shaping, and finally winding to obtain a PVA optical film; in: In step S1, the method for determining the solution foaming ability Hb and the solution defoaming ability Hd of the surfactant is: Step 1: Configure the concentration to 4.0×10 -4 g / mL, 5mL of surfactant solution is put into a sample bottle with a height of 7.5cm, an outer diameter of 2.5cm and a capacity of 15mL. The sample bottle is placed on the test table, which should be horizontal, with a black background and a ruler. The initial height H0 of the surfactant solution is read; Step 2: Wrap the sample bottle containing the surfactant solution to be tested in a dust-free cloth and put it into the centrifuge. Set the centrifuge speed to 3000r / min and the time to 5min. When using the centrifuge, pay attention to symmetrical placement and uniform weight; Step 3: After centrifugation, take out the sample bottle and quickly place it in front of a black background to read the height H1 of the highest position caused by the bubbles of the surfactant solution, Hb = H1-H0; Step 4: After standing for 2 hours, read the bubble height as H2, Hd = H1-H2; In step S2, after being dried by the casting roller, the moisture content of the film is controlled to be 20-30%; after being dried by the drying roller, the moisture content of the film is controlled to be 8-15%; after being heat-treated, dried and shaped, the moisture content of the film is controlled to be 0.1-5%.

2. The method for preparing a PVA optical film according to claim 1, characterized in that: In step S1, the PVA includes at least one of a polyvinyl alcohol homopolymer and a polyvinyl alcohol copolymer modified product.

3. The method for preparing a PVA optical film according to claim 1, characterized in that: In step S1, the content of the modified groups in the PVA is less than 10%; the average degree of polymerization of the PVA is 1500-3000; and the alcoholysis degree of the PVA is 98%-99.99%.

4. The method for preparing a PVA optical film according to claim 1, characterized in that: In step S1, the plasticizer includes at least one of glycerol, diglycerol, polyglycerol, ethylene glycol, and propylene glycol.

5. The method for preparing a PVA optical film according to claim 1, characterized in that: In step S1, the surfactant is a mixed surfactant of at least two of a nonionic surfactant and / or an anionic surfactant.

6. The method for preparing a PVA optical film according to claim 1, characterized in that: In step S2, during extrusion degassing, the barrel temperatures at both ends of the three-stage extruder are lower than the middle barrel temperature, and the middle barrel temperature is 90-130°C.

7. The method for preparing a PVA optical film according to claim 1, characterized in that: In step S2, during extrusion degassing, the GP pump inlet pressure of the three-stage extruder is 1.5-3 MPa, the GP pump speed is 40-80 rpm, and the pipeline temperature from the three-stage extruder to the die and the die temperature are 90-110°C.

8. The method for preparing a PVA optical film according to claim 8, characterized in that: In step S2, the temperature of the casting roller is 88-95°C; the number of the drying tanks is 8-20, the temperature of each roller is 30-90°C, and the temperature distribution shows a gradually decreasing trend.

9. The method for preparing a PVA optical film according to claim 8, characterized in that: In step S2, when heat treatment, drying and shaping are performed, a one-stage heat treatment or a multi-stage heat treatment is adopted according to the heat treatment time; when a multi-stage heat treatment is adopted, the temperature of each heat treatment stage tends to rise first and then fall.

10. A PVA optical film for a polarizer without in-plane linear light leakage, characterized in that: The PVA optical film is prepared by the preparation method of any one of claims 1-9.

Citation Information

Patent Citations

  • Polyvinyl-alcohol-based film, method for manufacturing same, polarizing film, and polarizing plate

    CN107073764A

  • Polyvinyl alcohol film for optical use, method for producing same, and polarizing film using same

    CN114252951A

  • Method for producing polyvinyl alcohol film for optical use

    CN114761200A

  • Polyvinyl alcohol optical film for polaroid and preparation method of polyvinyl alcohol optical film

    CN117946433A

  • Preparation method of PVA (Polyvinyl Alcohol) polarizing film base film with adjustable dyeing characteristic

    CN119099151A